Declarative System in Preventing the Criminalisation of Indigenous People for Adat Rights Conflicts in Indonesia - Cita Yustisia Serfiyani; Ari Purwadi; Ardhiwinda Kusumaputra (Faculty of Law, Sriwijaya University, Indonesia, 2022)
The existence of indigenous peoples as entities was born before the independence of the Republic of Indonesia. However, it is still disturbed by criminalisation by law enforcement officials for legal actions of indigenous peoples on their Adat lands whose Adat rights were transferred to other parties. Various regulations related to indigenous peoples already exist, and the Bill on Indigenous Peoples is not satisfying in preventing cases of criminalisation against indigenous peoples. It is because there is no adjustment in several crucial aspects, such as the nature of the recognition of indigenous people, protection of Adat lands and the application of criminal sanctions to achieve legal harmonisation in preventing the criminalisation of indigenous peoples. Synchronisation has not yet been realised between the substance of the legal rules related to indigenous peoples at the national level and the draft Bill on Indigenous Peoples with regional technical regulations at the sectoral level.This research uses statute and conceptual approaches to analyse legal norms, legal concepts, and legal principles related to indigenous people in Indonesia. As a result, it is believed that the protection of indigenous people's existence should be provided through a declarative system, not a constitutive system. It is also necessary to eliminate criminal sanctions against indigenous peoples in some related legal products according to the characteristics of indigenous peoples to stop the criminalisation of indigenous peoples and expand legal assistance for indigenous peoples in the context of implementing the law.